Public actions and policies in mangroves for the preservation of environmental (Research, Society and Development, 2021)
Ecosystems are the foundation of ecology. The relationship between them and man takes place through the use of their environmental services, which ends up in the breakdown of their resilience or depletion. In this aspect, mangroves are included, which are extremely important as a source of income for surrounding communities. The objective of this work was to discuss actions of its use and conservation and if there is integration with public policies in Brazil and in the world. The research carried out was exploratory. Mangroves are present among tropical areas, mainly between latitudes 30° N and 30° S, with Brazil having approximately 13,989 km² of this feature on its coast, with 87% present in the interior of Conservation Units. It was noticed that, in Brazil, the law is still adapting to the need to protect these ecosystems, changing the concepts present in its letters for preservation over the years. In the United States, Florida laws show a focus on sustainable development. The valuation of mangroves is important in establishing public policies and investments, benefiting communities involved with them. The Ramsar convention establishes ways of sustainable use of wetlands in several countries. This convention makes no distinction between areas, and in Brazil the laws emulate it, where mangroves share the same considerations as other features. It was noticed that Brazilian legislation for mangroves does not have specificities that deal with their sustainable use, but that the projects created in these areas have very important and satisfactory results.